Rapid development of two factor IXa inhibitors from hit to lead. Issue 11 (1st June 2015) - Parker, Dann L.; Walsh, Shawn; Li, Bing; Kim, Esther; Sharipour, Aurash; Smith, Cameron; Chen, Yi-Heng; Berger, Richard; Harper, Bart; Zhang, Ting; Park, Min; Shu, Min; et al.
Graphical abstract: Abstract: Two high-throughput screening hits were investigated for SAR against human factor IXa. Both hits feature a benzamide linked to a [6-5]-heteroaryl via an alkyl amine. In the case where this system is a benzimidazolyl-ethyl amine the binding potency for the hit was improved >500-fold, from 9 μM to 0.016 μM. For the other hit, which contains a tetrahydropyrido-indazole amine, potency was improved 20-fold, from 2 μM to 0.09 μM. X-ray crystal structures were obtained for an example of each class which improved understanding of the binding, and will enable further drug discovery efforts.